2003
DOI: 10.1167/iovs.02-0697
|View full text |Cite
|
Sign up to set email alerts
|

New Locus for Autosomal Dominant High Myopia Maps to the Long Arm of Chromosome 17

Abstract: A novel putative disease locus for AD high-grade myopia has been identified and provides additional support for genetic heterogeneity for this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
74
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(75 citation statements)
references
References 30 publications
1
74
0
Order By: Relevance
“…2,3 High myopia (4À6.0 D) can result in severe ocular morbidity, and extreme myopia (410.0 D) exhibits complications that potentially manifest in blindness, such as retinal detachment, macular degeneration, and glaucoma. 4 Early identification of patients predisposed to high or extreme myopia, particularly children, is important so that preventive measures can be taken.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 High myopia (4À6.0 D) can result in severe ocular morbidity, and extreme myopia (410.0 D) exhibits complications that potentially manifest in blindness, such as retinal detachment, macular degeneration, and glaucoma. 4 Early identification of patients predisposed to high or extreme myopia, particularly children, is important so that preventive measures can be taken.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, COL1A1 can be a candidate gene for myopia. Although Paluru et al (2003) did not find causal mutations in the coding region of COL1A1, this does not completely exclude a possibility of a polymorphism in the non-coding region conferring a risk for myopia. We conducted a case-control study to test for the COL1A1 gene as a susceptibility locus to high myopia.…”
Section: Introductionmentioning
confidence: 67%
“…Genetic variants at the type I collagen a-1 gene (COL1A1) may influence gene expression, which causes different susceptibilities to myopia. Paluru et al (2003) reported a linkage of high myopia to 17q21-22, where COL1A1 is located. Accordingly, COL1A1 can be a candidate gene for myopia.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of myopia has been reported as high as 70-90% in certain Asian countries, 30-40% in Europe and the US, and 10-20% in Africa (3,(5)(6)(7)(8)(9)(10). Its extreme form, high myopia, is the fourth most common cause of irreversible blindness in the world (11,12).…”
Section: Introductionmentioning
confidence: 99%